Cyanocarbazole-substituted di(9H-carbazol-9-yl)-1, 1'-biphenyl derivatives for efficient blue phosphorescent host materials for organic light emitting diodes. Issue 1 (11th February 2022) - Woo, Jeongkyu; Han, Ju Hee; Kim, Ki Ju; Moon, Yu Ji; Kim, Young Kwan; Yoon, Seung Soo
Abstract: To develop the efficient blue phosphorescent host materials for Organic light-emitting Diodes (OLEDs), cyanocarbazole-substituted 3', 5'-di(9 H -carbazol-9-yl)-1, 1'-biphenyl derivatives are designed and synthesized. Multilayer devices were fabricated in the following sequence; ITO (180 nm)/Tris(4-carbazoyl-9-ylphenyl)amine (TCTA) (75 nm)/Blue phosphorescent host materials (15 nm)/Bis[2-(4, 6-difluorophenyl)pyridinato- C 2, N ](picolinato)iridium(III) (Firpic) (15 nm)/1, 3, 5-Tri(m-pyridine-3-ylphenyl)benzene (TmPyPB) (40 nm)/Liq (2 nm)/Al (100 nm). In particularly, blue phosphorescent device using 9-(3', 5'-di(9 H -carbazol-9-yl)-[1, 1'-biphenyl]-4-yl)-9 H -carbazole-3-carbonitrile as a host material exhibited efficient emission with a luminous efficiency, a power efficiency, an external quantum efficiency, and CIE coordinates of 11.6 cd/A, 4.10 lm/W, 5.62% at 20 mA/cm 2, and (0.15, 0.33) at 8 V, respectively.